Taphonomy of benthic foraminiferal tests from the Jurujuba Sound, Guanabara Bay, Rio de Janeiro, Brazil - Kfouri-Cardoso, Patricia B. P.; Simões, Marcello Guimarães; Rodrigues, Sabrina Coelho; Eichler, Beatriz Beck; Sousa, Silvia Helena de Mello e; Eichler, Patrícia Beck; Figueira, Rubens César Lopes (Anuário do Instituto de Geociências, 2006)
Abstract